Micro-scale CFD study about the influence of operative parameters on physical mass transfer within structured packing elements - Sebastia-Saez, Daniel; Gu, Sai; Ranganathan, Panneerselvam; Papadikis, Konstantinos (Elsevier, 2014)
In this work a VOF-based 3D numerical model is developed to study the influence of several operative parameters on the gas absorption into falling liquid films. The parameters studied are liquid phase viscosity, gas phase pressure and inlet configuration, liquid-solid contact angle and plate texture. This study aims to optimize the post-combustion CO2 capture process within structured packed columns. Liquid phase viscosity is modified via MEA (i.e. monoethanolamine) concentration. The results show that an increase in liquid viscosity reduces the diffusivity of oxygen within the liquid film thus hindering the efficiency of the process. Higher pressure carries an absorption improvement that can be attractive to be applied in industry. The simulations show that enhanced oxygen absorption rates can be achieved depending on the velocity of the gas phase and the flow configuration (i.e. co- and counter-current). Also, the importance of wetting liquid-solid contact angles (i.e. less than 90°) is highlighted. Poor liquid-solid adhesion has similar effects as surface tension in terms of diminishing the spreading of the liquid phase over the metallic plate. Finally the influence of a certain geometrical pattern in the metallic surface is also assessed.